Productivity of tomato hybrids due to the application of calcium silicate - Coutinho, Pablo Wenderson Ribeiro; Echer, Márcia de Moraes; Guimarães, Vandeir Francisco; Lana, Maria do Carmo; Alves, Thatiane Nepomuceno; Inagaki, Adriano Mitio (Scientia Agraria Paranaensis, 2020)
Silicon is a beneficial nutrient for the growth and production of many plant species, including tomatoes. The objective was to evaluate the influence of calcium silicate on the morphophysiological characteristics of tomatoes and the absorption of silicon, calcium, and magnesium. The experiment was conducted in a protected environment from August to December 2017, in a random block design, in a 2 x 5 factor scheme, with four repetitions. The first factor consisted of two hybrids (Ivety and Natalia) and the second factor by doses of calcium silicate (0, 150, 300, 450 and 600 kg ha-1). The fruits were evaluated for number of fruits per plant, longitudinal and transversal diameter, average fruit mass, commercial, non-commercial, and total productivity. The plants were evaluated for number of leaves, stem diameter, plant length, leaf area, membrane integrity damage, lignin content, stem and leaves dry mass, silicon accumulation and content, calcium, and magnesium contents in the leaves and in tomato fruits. The morphometric characteristics of Ivety and Natalia tomato hybrids were not altered by increasing doses of calcium silicate. The increased doses of calcium silicate influenced the non-commercial productivity of the tomato fruits, showing a reduction of this with the increased doses. Calcium silicate influenced differently in each hybrid, and it is worth noting that these results may vary in terms of genetic material and cultivation environment.